Specificity and Plasticity of the Functional Ionome of Brassica napus and Triticum aestivum Subjected to Macronutrient Deprivation - Courbet, Galatéa; D’Oria, Aurélien; Lornac, Aurélia; Diquélou, Sylvain; Pluchon, Sylvain; Arkoun, Mustapha; Koprivova, Anna; Kopriva, Stanislav; Etienne, Philippe; Ourry, Alain (Frontiers in Plant Science, 2021)
The composition of the functional ionome was studied in Brassica napus and Triticum aestivum with respect to the response of 20 elements under macronutrient deprivation. Analysis of relative root contents showed that some nutrients, such as Fe, Ni, Cu, Na, V, and Co, were largely sequestered in roots. After 10 days of deprivation of each one of these 6 macronutrients, plant growth was similar to control plants, and this was probably the result of remobilization from roots (Mg and Ca) or old leaves (N, P, K, S). Some tissue concentrations and net nutrient uptakes into roots were either decreased or increased, revealing multiple interactions (93 in wheat, 66 in oilseed rape) that were common to both species (48) or were species specific. While some interactions have been previously described (increased uptake of Na under K deficiency; or increased uptake of Mo and Se under S deficiency), a number of new interactions were found and some key mechanisms underlying their action have been proposed from analysis of Arabidopsis mutants. For example, nitrate uptake seemed to be functionally linked to Na(influx, while the uptake of vanadium was probably mediated by sulfate transporters whose expression was stimulated during S deprivation.